Delayed Early Season Irrigation: Impacts on Hop Yield and Quality. (10th January 2022) - Gent, David H.; Claassen, Briana J.; Massie, Stephen T.; Phillips, Claire L.; Shellhammer, Thomas H.; Trippe, Kristin M.; Twomey, Megan C.
Abstract: Irrigation is essential for hop production in the Pacific Northwestern United States, the primary growing region in the U.S. Irrigation water supplies can be inadequate in drought years and may become more variable in the future due to climate variability and increasing non-agricultural demand. In this research, the impact of delayed timing of the first irrigation of the season on hop yield and cone quality metrics in the cultivars Cascade and Zeus over three years was evaluated. The impact of delayed irrigation depended on year and cultivar, with larger impacts on yield of Cascade as compared to Zeus in this study. In Cascade, yield decreased 10.8% to 16.2% when the timing of the first irrigation was delayed by 10 or 18 days after training, respectively. However, cone quality factors were statistically similar when data were aggregated over all three years. In Zeus, delaying the first irrigation did not have detectable effects on brewing quality or yield in any individual year or when data were aggregated over all years. Thus, while even a brief delay in irrigation may substantially reduce yield in some cultivars such as Cascade, these effects were cultivar-dependent and impacts on brewing quality appeared small or undetectable.